2008
DOI: 10.1016/j.neuroimage.2008.04.234
|View full text |Cite
|
Sign up to set email alerts
|

Sensory stimulation activates both motor and sensory components of the swallowing system

Abstract: Volitional swallowing in humans involves the coordination of both brainstem and cerebral swallowing control regions. Peripheral sensory inputs are necessary for safe and efficient swallowing, and their importance to the patterned components of swallowing has been demonstrated. However, the role of sensory inputs to the cerebral system during volitional swallowing is less clear. We used four conditions applied during functional magnetic resonance imaging to differentiate between sensory, motor planning, and mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
94
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 58 publications
16
94
0
1
Order By: Relevance
“…Furthermore, increasing capsaicin levels leads to a reliable increase in estimates of this urge (Davenport, Sapienza, & Bolser, 2002). Similarly, in our own unpublished studies of the effects of oropharyngeal stimulation on the urge-to-swallow, we have found that oropharyngeal stimulation using pulses of air produces both an urge-to-swallow and overt swallowing (for similar findings, see also Lowell et al, 2008). More importantly, we have found that increasing the intensity of oropharyngeal stimulation leads to an increase in the strength of the perceived urge-to-swallow.…”
Section: How Are Urges Related To Awareness?supporting
confidence: 76%
“…Furthermore, increasing capsaicin levels leads to a reliable increase in estimates of this urge (Davenport, Sapienza, & Bolser, 2002). Similarly, in our own unpublished studies of the effects of oropharyngeal stimulation on the urge-to-swallow, we have found that oropharyngeal stimulation using pulses of air produces both an urge-to-swallow and overt swallowing (for similar findings, see also Lowell et al, 2008). More importantly, we have found that increasing the intensity of oropharyngeal stimulation leads to an increase in the strength of the perceived urge-to-swallow.…”
Section: How Are Urges Related To Awareness?supporting
confidence: 76%
“…2006; Lowell et al. 2008); however, sensation from these structures is mediated by the glossopharyngeal nerve (CN IX), stimulation of which is already known to be able to elicit a swallow. In addition to afferent input from CN X and CN IX, the NTS receives sensory input from the oral tongue via fibers of the chorda tympani branch of the facial nerve (CN VII) for taste on the anterior two‐thirds of the tongue.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific articles were categorized specific features to the swallowing cortical representation (3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . Research on elderly and patients with dysphagia underwent compared to control groups.…”
Section: Population Studiedmentioning
confidence: 99%